Numerical Analysis on Fatigue Performance in Fillet Weld Roots of Steel Bridge Bearings - Mao, Jiahao; Jiang, Feng; Hirohata, Mikihito; Qin, Yanyue (Salehan Institute of Higher Education, 2025)
Fillet weld roots near bridge supports are critical fatigue-prone details in steel bridges, particularly under high stress concentration. Fatigue cracks at these locations tend to be initiated internally, where detection and repair remain challenging with current techniques. Fatigue performance improvements are explored from the perspectives of structural design and epoxy insertion. Five actual bridges in the USA, China, and Japan were analyzed using a hybrid finite element modeling approach, employing low-precision girder models for load distribution and high-precision local support models with an introduced notch for Effective Notch Stress (ENS) evaluation. Both actual bridge case studies and numerical parametric analyses were conducted. Results indicate that increasing weld size effectively reduces ENS, while sole plate thickness has a limited effect. Bolts play a pivotal role in limiting relative displacement between the bottom flange and the sole plate, though their constraint range is localized. To address the limited effectiveness of structural adjustments, adhesive filling was introduced in areas beyond the bolt constraint range. Bonding-assisted welding with epoxy insertion achieved up to a 56% reduction in ENS and significantly improved fatigue performance. The findings confirm the potential of bonding-assisted welding for improving the durability of fillet weld roots in steel bridge supports and provide practical solutions to the difficult-to-detect root fatigue cracks.